Discussion on Sociolinguistic Dynamism: The Case of Kanuri Lexical Borrowing from Hausa in Damagaram - Aichatou, Aboubakar Nana (New Horizons in Education and Social Studies Vol. 9, 2021)
One of the most frequently encountered products of cultural contact is the borrowing. Borrowing is seen to be a source, an important source of language enrichment as well as of language endangerment. When a given language borrows a great amount of lexical terms from another language, we assume that the two languages have the same attributes or else they have been in contact for a long time. As a result, the current study investigates the Kanuri borrowed words from Hausa. The study is limited to what lexical terms have been borrowed by the Kanuri from the Hausa, how has the borrowing come about as all languages have the means to create, enrich themselves out of their own resources. In other words, why do the Kanuri people borrow a word or words from the Hausa while they have a fully equivalent beforehand? In this research, the researcher collected the data by taking notes and later arranged as documentations for further analysis. Finally, the researcher finds that actually many consider the Kanuri borrowed terms from the Hausa as typically Kanuri and could not dissociate them with other Kanuri words. For any language, in general, and Kanuri language, in particular, to survive, to meet its lexical need and become a great vector of development in the socio economic and political arena, it has to create, recreate itself, that is to have the necessary and adequate words and expressions to convey the desired concepts and contexts and to keep pace with the advancement of technology. Hence, the necessity for the current study to bring out the endangerment of borrowing for the Kanuri people and point out the necessity for the language to coin new words (neologism) that could better enrich its lexicon.